Ethical Concern of Brain–Computer Interfaces - Zdravkova, Katerina (My University, 2015)
Brain-computer interfaces enable a communication between neuromuscular system and peripheral nerves and muscles. They are implemented to establish or improve the missing or lost functions of the disabled, or to enhance the functions of healthy people. Brain implants interfere the natural brainhuman interaction, raising various ethical questions. This paper presents some of them, intending to increase the awareness of their prospective erroneous or dishonest use.